Understanding The Reform Of Public Transit In India - et.al, Deepshikha Jain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cities are the major sources of urban and economic development in developing countries and Transit Oriented Development (TOD) is broadly recognized as a policy to avoid congestion on major junctions, routes of an area by majorly focusing utilization of public transit, particularly making people walk and use non- motorized transport (NMT) specifically to make city environmentally sustainable. Be that as it may, TOD has to a great extent been a trendy expression in Indian strategy records for over 10 years, as the nation still anticipates its first completely executed TOD project. Thus, the main objective of this paper is to evaluate this strategy by understanding the feasibility this concept through two important TOD case studies of Delhi and Ahmadabad where the former has TOD in planning stage while the other in implemented. Thus, this paper will demonstrate the reforming of Indian city to a public transit oriented (PTO).